Black Orpheus : music in African American fiction from the Harlem Renaissance to Toni Morrison - Simawe, Saadi (Garland reference library of the humanities, 2000)
In twentieth-century African American fiction, music has been elevated to the level of religion primarily because of its power as a medium of freedom. This collection explores literary invocations of music.